ChemInform Abstract: An Efficient Synthesis of Polyfunctionalized Indole Derivatives via Three‐Component Domino Reaction Catalyzed by L‐Proline. Issue 49 (December 2015) - Fu, Lei; Lin, Wei; Huang, Zhi‐Bin; Shi, Da‐Qing
Abstract: Two rings and four bonds are efficiently formed by an facile one‐pot procedure leading to the desired indole derivatives in excellent yields.